The Effect of Naphtaleine Acetic Acid ND Benzyl Amino Purine on the Subculture of Kepok Unti Sayang Banana - Samanhudi, Samanhudi; Setyawati, Andriyana; Purwanto, Edi; Rahayu, Muji; Eviani, Eviani; Cahyadi, Muhammad Aji (Journal of Biodiversity and Biotechnology, 2025)
The Kepok Unti Sayang variety is a superior type of banana that is resistant to fusarium wilt. The high demand for Kepok Unti Sayang needs to be balanced with good seed production. One of the methods used for multiplying superior seeds of Kepok Unti Sayang is through tissue culture. This research aims to obtain the optimal concentration of Naphtaleine Acetic Acid (NAA) in the subculture media for the growth of root numbers in the Kepok Unti Sayang Banana. The second objective is to determine the optimal concentration of Benzyl Amino Purine (BAP) in the subculture medium for shoot number growth in Kepok Unti Sayang bananas. Another goal is to identify the best treatment combination that can produce the highest number of shoots in Kepok Unti Sayang bananas. The research was conducted at the Laboratory of Plant Physiology and Biotechnology at Sebelas Maret University from February to July 2025. The study was conducted with 4 levels of NAA treatment: 0; 0.5; 1; and 1.5 ppm. The BAP treatment was administered at 4 levels: 0; 1; 2; and 3 ppm. The variables observed in this study were the time of shoot emergence, number of shoots, time of root emergence, root length, and final height of the planlet. Data from each variable were then analyzed using analysis of variance (ANOVA) with an F-test at a significance level of 95%. Significantly different data were then followed by Duncan's Multiple Range Test (DMRT) at a significance level of 95%. The significant combination of NAA and BAP on the observed variables was then reanalyzed using regression tests. The results showed that the application of various concentrations of NAA does not affect the growth of the number of roots of Kepok bananas var. Unti Sayang. The application of 2 ppm BAP is optimal for the growth of the number of shoots of Kepok bananas var. Unti Sayang. The interaction between 1 ppm NAA and BAP at 1-2 ppm produces the most optimal average shoot emergence time.